Effectiveness of Election Special Judiciary Towards 2019 Presidential Election - Marpaung, Jerico Mathias; Pradana, Tirta Mulya Wira (Law Research Review Quarterly, 2018)
Indonesia as a democratic country that implemented the electoral system since 1955. Caused the world of politics in Indonesia to become more mature. Democratic practices developed from the reform era to the present. The general election which is a means of democracy is not far from political deviations, one of which is the black campaign. Special election judiciary exists with the aim of protecting the constitutional rights of citizens in elections, provide legal space for those who have been harmed in the implementation of elections, get legal certainty in the life of a democratic country, and as an effort to accelerate the settlement of disputes or cases during the general election process. Democracy in Indonesia can now be said to be comparatively well established but actually has a fairly shaky foundation, where the power of the people who should be united from below is taken from above (Top-Down democracy consolidation). For this reason, a special election court exists to examine, hear and decide on certain cases which can only be established in one of the judicial bodies under the Supreme Court regulated in the law. Special election court is important to maintain stability in politics. The idea of ​​a Special Election Court is actually one of the most important components in the principles of election administration, namely "legal certainty".